Longitudinal study on skeletal changes during and after bionator therapy using metallic implants - André da Costa Monini; Luiz Gonzaga Gandini Júnior; Lídia Parsekian Martins; Dirceu Barnabé Raveli (Universidade Estadual de Campinas, 2015)
Aim: To demonstrate the magnitude and direction of skeletal changes in the maxilla and mandible during and after the use of bionator, as well as their rotations. Methods: Partial superimposition on the maxilla and mandible on the metallic implants and total superimposition on the cranial base were performed at three periods, T1 before bionator therapy, T2 after bionator therapy, and T3 5.68 years after T2. Results: There was total clockwise maxillary rotation and counterclockwise mandibular rotation, in the North American technique, throughout the study period, as well as extensive remodeling on the condylar region, especially in vertical direction and on the gonial region in horizontal direction. Conclusions: The total maxillary rotation seemed to be significantly affected by therapy than the mandible. There was a clear change in the direction of condylar remodeling compared to the period of bionator therapy and posterior bionator therapy. Considering the entire study period, it was observed that intra-matrix rotation of the maxilla and mandible masked their total rotation, causing minimum changes in the matrix rotation.